Voices and Visions from the Margins on Mission and Unity: A disability-informed reading of the Pauline metaphor of the church as the body of Christ - George, Samuel (International review of mission, 2011)
Disability studies from a missional perspective in the Indian context are rare. Mission and unity cannot be “talked” about without the active inclusion of those in the margins; rather, they are the subject of mission and unity of the church which, in Pauline language, is the body of Christ. With the help of a disability-informed reading of the Pauline metaphor of church as the body of Christ, an attempt is made to understand the integral constituent of this “body” and its mission and unity. Our deliberations on the metaphor of body make it amply clear that “weaker” members are indispensable for the mission and unity of the church. They are the paradigm for the manifestation of God. Mission and unity of the church depend on the inclusion and equal participation of the margins—the disabled.